The value of combined positron emission tomography/magnetic resonance imaging to diagnose inflammatory bowel disease: a prospective study. (July 2021) - Tenhami, Mervi; Virtanen, Johanna; Kauhanen, Saila; Koffert, Jukka; Kemppainen, Jukka; Saunavaara, Virva; Kujari, Harry; Hurme, Saija; Teperi, Simo; Voutilainen, Markku
Background: The clinical utility of positron emission tomography/magnetic resonance imaging (PET/MRI) in comparison to standard work-up with patients with known or suspected inflammatory bowel disease (IBD) is unknown. Purpose: To evaluate the value of 18F-fluorodeoxyglucose (18F-FDG) PET/MRI in the diagnostics of IBD and further compare the data obtained using PET/MRI to histological findings. Materials and Methods: Ten patients with relapse in IBD or with symptoms of suspected IBD were recruited either from a gastroenterology outpatient clinic or from a hospital ward. Intestinal inflammation was assessed with histology and 18F-FDG PET/MRI. Maximum standard uptake values (SUVmax ) were calculated in six regions of the intestine (small bowel, ascending, transverse, descending and sigmoid colon, and rectum) and compared to histological analysis of inflammation activity. Results: The study showed that both the inflammation activity ( P = 0.008) and the region of the biopsy in the intestine ( P = 0.015) had a significant effect on SUV. SUVs obtained from severe inflammation activity emerged significantly from the background ( P = 0.006). In addition, the SUVs obtained from moderate inflammation raised from background, but the difference was not statistically significant ( P = 0.083), while SUVs of mild inflammation were at the same level with SUVs of normal bowel wall ( P = 0.988). Conclusion: 18F-FDG PET/MRI is a promising method of detecting especially severe inflammatory bowel lesions. More data are required to define its sensitivity and specificity.